Brown Adipose Tissue - role in metabolic disorders - Haq, Tahniyah; Ong, Frank Joseph; Kanji, Sarah (IMC Journal of Medical Science, 2019)
Brown adipose tissue, a thermogenic organ, previously thought to be present in only small mammals and children has recently been identified in adult humans. Located primarily in the supraclavicular and cervical area, it produces heat by uncoupling oxidative phosphorylation due to the unique presence of uncoupling protein 1 by a process called nonshivering thermogenesis. BAT activity depends on many factors including age, sex, adiposity and outdoor temperature. Positron-emission tomography using 18F-fluorodeoxyglucose and computed tomography (18F-FDG PET–CT), magnetic resonance imaging (MRI) and thermal imaging (IRT) are among several methods used to detect BAT in humans. The importance of BAT is due to its role in whole body energy expenditure and fuel metabolism. Thus it is postulated that it may be useful in the treatment of metabolic diseases. However, there are still many unanswered questions to the clinical usefulness of this novel tissue. IMC J Med Sci 2019; 13(1): 002